If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14(t + -5) + 7t = 7(3t + 5) + -13 Reorder the terms: 14(-5 + t) + 7t = 7(3t + 5) + -13 (-5 * 14 + t * 14) + 7t = 7(3t + 5) + -13 (-70 + 14t) + 7t = 7(3t + 5) + -13 Combine like terms: 14t + 7t = 21t -70 + 21t = 7(3t + 5) + -13 Reorder the terms: -70 + 21t = 7(5 + 3t) + -13 -70 + 21t = (5 * 7 + 3t * 7) + -13 -70 + 21t = (35 + 21t) + -13 Reorder the terms: -70 + 21t = 35 + -13 + 21t Combine like terms: 35 + -13 = 22 -70 + 21t = 22 + 21t Add '-21t' to each side of the equation. -70 + 21t + -21t = 22 + 21t + -21t Combine like terms: 21t + -21t = 0 -70 + 0 = 22 + 21t + -21t -70 = 22 + 21t + -21t Combine like terms: 21t + -21t = 0 -70 = 22 + 0 -70 = 22 Solving -70 = 22 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 14(t-5)+7t=t(3t+5)-13 | | 20m^2=-2m^3-50m | | -4(-2x+3)=12 | | 4x^2-12x=16 | | 9y-2y=14 | | 2a=2 | | 1.6x=8 | | X^3+24x^2+144x=0 | | c^2-24c+82=0 | | 2x^3y^3-24x^2y^4+72xy^5=0 | | 3x+2=2x^2 | | x-7.6=6.6 | | y+38=13 | | x(x-6)+1=x-11 | | (5x-2)(2x+3)=10 | | X^4+2x^3-x-2=0 | | 3=6x+y | | X^3+18x^2+45=0 | | 4x(x-3)+5=0 | | 24x^2+100x-36=0 | | 4ln(7x)=24 | | 35x^2-55x-30=0 | | 30x^2-8x-8=0 | | 6x^2=x+1 | | 5x^2+30x-135=0 | | 3ln(7x)=18 | | x^2+3x+30=0 | | 3x^2+33x+90=0 | | 12(t-3)+3t=5(3t+3)-8 | | X^2+16y^2+6x-64y+57=0 | | 4v^2+12v-72=0 | | 3x^2+33x+30=0 |